PENGARUH MEDIA PERMAINAN MENCOCOKAN KATA TERHADAP PEMAHAMAN & KEAKTIFAN BELAJAR SISWA SD KLS 6 PADA MATERI BAHASA INDONESIA DI SD PEJAGAN 1 BANGKALAN - Dela Agustin; Ihwan Firmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This work is part of the Elementary School Teacher Education Study Program, under the guidance of Ihwan Firmansyah, M.Pd.. This study aims to examine the impact of implementing learning media in the form of word matching games on the understanding and learning activity of sixth grade students at SDN Pejagan 1 Bangkalan. The approach used is quantitative research with a one group pretest-posttest design, which allows for the evaluation of changes before and after the intervention. Data collection techniques involved the use of questionnaires and test questions, while the validity of the instruments was tested through validity and reliability analysis. Data analysis methods included normality tests and paired sample t-tests to determine the significance of differences. The results of the paired sample t-test on learning activity showed a significant value of 0.000, which is less than 0.05, so it can be concluded that the word matching game media has a significant effect on increasing student learning activity. Similarly, the paired sample t-test for learning comprehension produced a significant value of 0.000, which is also below 0.05, indicating a positive effect of this media on the comprehension of Indonesian language material. These findings underscore the potential of interactive media in enriching the learning process at the elementary school level.